Effects of dietary protein sources and levels on uric acid metabolism, renal function, and inflammatory responses in goslings - Chen, Yuanjing; Yang, Zhengfeng; Su, Guoqiang; Li, Ning; Yang, Haiming; Wang, Zhiyue (Frontiers in Veterinary Science, 2025)
Dietary protein plays a crucial role in poultry nutrition, influencing nitrogen metabolism, renal function, and immune responses. This study investigated the effects of dietary protein source (plant-based vs. animal-based) and level (14.5, 18.5, and 22.5%) on serum biochemical parameters, renal metabolic markers, inflammatory cytokines, and gene expression in Jiangnan White goslings from day 1 to day 30 of age. A 2 × 3 factorial design was employed with 504 goslings randomly assigned to six groups, each comprising six replicates with 14 goslings per replicate. The results showed that dietary protein level significantly influenced serum uric acid (UA), creatinine (Cr), urea nitrogen (UN), and xanthine oxidase (XOD) activity, with goslings fed a high-protein diet (22.5%) exhibiting the highest levels (p < 0.05). Increased dietary protein also led to significantly elevated renal UA concentrations and XOD activity, particularly at 22 and 30 days (p < 0.05). In contrast, dietary protein source had limited influence on metabolic parameters, with only a transient difference in serum UA and Cr observed at 10 days of age (p < 0.05), and no significant effects on other serum or renal markers (p > 0.05). Additionally, renal inflammatory cytokines (IL-1β, IL-8, TNF-β) were significantly influenced by protein level, whereas XDH, BCL-2, and GLUT-9 mRNA expression remained unchanged (p > 0.05). No significant interactions between protein source and level were observed for most metabolic parameters, except for Cr and TNF-β. These findings suggest that total protein intake, rather than protein source, is the primary regulator of nitrogen metabolism and renal health in goslings. Optimization of protein levels is essential to balance growth performance and metabolic homeostasis.